Penerapan Kompetensi Kewirausahaan Kepala Sekolah - Miftahul Jannah; Sumarlin Mus; Irmawati Irmawati (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This research examines how to apply the entrepreneurial competence of principals at SMKN 6 Pangkep, which is focused on school development innovation. The purpose of this study was to determine how principals' entrepreneurial competence in creating innovations that are useful for school development at SMKN 6 Pangkep. This research approach is nonionic qualitative with a descriptive research type—data collection techniques in the form of interviews, observations, and documentation. The interview data analysis technique uses data reduction, data exposure, drawing conclusions and checking the validity of the data using the triangulation technique. The result showed the application of principals' entrepreneurial competence in school development innovation. School development innovation can be seen in the principal’s ability to act creatively and innovatively, empower school competencies, and foster an entrepreneurial spirit. The form of creative and innovative actions taken by the principal is to create a comparative advantage, the state of empowering school potential carried out by the principal is through the utilization of existing natural resources related to culture in school and the form of fostering an entrepreneurial spirit by the principal is applied through entrepreneurial learning, industrial work practice activities, and school business unit management.